Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $W_t$ be a Brownian motion and

$$ M_t = \max_{o<s<t} W_s $$

Can anyone give me some insights on how to prove:

$$ P[M_t >a \mid W_t=M_t]= \exp(-a^2/2t) \quad;\quad a>0 $$

Many thanks in advance.

share|cite|improve this question
up vote 4 down vote accepted

The joint distribution of $(B_t, M_t)$ is well-known. The probability density reads: $$ f_{(B_t, M_t)}(x,y) = \sqrt{\frac{2}{\pi}} \frac{2y-x}{t^{3/2}} \exp\left(-\frac{(2y-x)^2}{2t} \right) [ y>0, x \leqslant y ] $$ where $[ y>0 ]$ denotes Iverson bracket.

From here the distribution of $(M_t, M_t-B_t)$ is easy to read off: $$ f_{(M_t, M_t-B_t)}(x,y) = \sqrt{\frac{2}{\pi}} \frac{x+y}{t^{3/2}} \exp\left(-\frac{(x+y)^2}{2t} \right) [ y>0, x > 0 ] $$ Now finding the conditional probability density is also straightforward. Assuming $y>0$: $$ f_{M_t|M_t-B_t}(x|y) = \frac{f_{M_t,M_t-B_t}(x,y)}{f_{M_t-B_t}(y)}= \frac{x+y}{t} \exp\left(-\frac{x(x+2y)}{t} \right) [x >0] $$ This will now allow you to find the quantity of interest: $$ \mathbb{P}\left(M_t > a |B_t=M_t\right) = \mathbb{P}\left(M_t > a |M_t - B_t=0\right) = \lim_{y \to 0^+} \int_{a}^\infty f_{M_t|M_t-B_t}(x,y) \mathrm{d}x = \lim_{y \to 0^+} \exp\left(-\frac{a(a+2y)}{2t} \right) = \mathrm{e}^{-\frac{a^2}{2t}} $$

share|cite|improve this answer
@MichaelChernick Thank you for the edits, and sorry for being sloppy in my grammar. – Sasha Sep 12 '12 at 17:04
I have a follow up question: Is there a simple proof for the joint density of $(M_t, B_t)$ that Sasha gives above? – Ben Sep 12 '12 at 21:33
@Ben See sect. 3.8 of Fima Klebaner's "Introduction to Stochastic Calculus with Applications". Reflection principle is used to evaluate $\mathbb{P}\left(B_t \leq x, M_t \geq y\right)$ and is found to be $1-\Phi\left((2y-x)/\sqrt{t}\right)$. The density follows by differentiation. – Sasha Sep 12 '12 at 21:38
@Sasha. Thanks. – Ben Sep 13 '12 at 10:20

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.